2001
DOI: 10.1038/sj.sc.3101173
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar myxopapillary ependymoma mimicking neurofibroma

Abstract: Objective: To report a case of lumbar myxopapillary ependymoma in whom neuroradiological and surgical ®ndings strongly suggested neuro®broma. Clinical presentation: The patient presented with a 2 year history of progressive monoparesthesia and monoparesia of his right leg. He reported having minimal fecal and urinary incontinence. Intervention: Total resection of the tumor was achieved by total L1-L2 laminectomies. There was no attachment to the spinal cord and dura. Conclusion: In spite of contemporary sophis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
(5 reference statements)
3
11
0
6
Order By: Relevance
“…El diagnóstico diferencial debe hacerse con otros tumores de la misma localización, como astrocitomas, paragangliomas del filum 13 , schwannomas 4,6 , epidermoides, etc. El tratamiento microquirúrgico es el de elección en los tumores de esta localización.…”
Section: Discussionunclassified
“…El diagnóstico diferencial debe hacerse con otros tumores de la misma localización, como astrocitomas, paragangliomas del filum 13 , schwannomas 4,6 , epidermoides, etc. El tratamiento microquirúrgico es el de elección en los tumores de esta localización.…”
Section: Discussionunclassified
“…Bavbek et al [16] reported a 46-year-old man with a 2 year history of progressive paresthesia and paresis of the right leg. Lumbar spinal MRI showed an intradural extramedullary mass with homogenous postcontrast enhancement at L1−L2.…”
Section: Discussionmentioning
confidence: 99%
“…Of the intradural ependymomas, approximately 50% are intramedullary, above the conus, and the remaining 50% occur in association with the terminal filum, cauda equina, and conus medullaris. 3,6,22 In the lumbosacral region, ependymomas account for 90% of intradural tumors.10 In addition to occurring intradurally, ependymomas can also sometimes occur extradurally around or in the sacrum.Spinal ependymomas are most common in the fourth decade of life and are more common in male patients. 5,33,37 Sonneland, et al, 32 reported a 1.7:1.0 male/female ratio and a mean age at onset of 36.4 years (range 6-82 years) in the largest series (77 patients) of myxopapillary ependymomas reported in the literature.…”
mentioning
confidence: 99%
“…Of the intradural ependymomas, approximately 50% are intramedullary, above the conus, and the remaining 50% occur in association with the terminal filum, cauda equina, and conus medullaris. 3,6,22 In the lumbosacral region, ependymomas account for 90% of intradural tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation